Power Dissipation Reduction System for Adjustable Power Supplies - Valeriu Savu; Madalin Ion Rusu; Dan Savastru; Dragos Manea (Energies)
The design of high-power sources intended for domestic consumption in the case of renewable energies, research laboratories, the operation of diode-pumped lasers, electric vehicles, etc. requires reducing the price, increasing efficiency, reducing overall dimensions, and so on. Achieving these requirements applicable to the manufacture of high-power sources represents a challenge in research, which leads to new concepts for the realization of these sources. The present work aims to improve the parameters of high-power adjustable linear voltage sources, also presenting practical results and simulations. The combined source designed and realized by us combines two systems, one commutative and the other linear. Both the simulated and practical results showed that the new combined source that we propose dissipates up to 10 times less power than a linear source designed for the same output and power supply parameters under the same conditions.